Does Stock Market Development Enhance Private Investment in Ghana? - Ofori-Abebrese, Grace; Amporfu, Eugenia; Adu, George (International Journal of Humanities and Social Science Research, 2016)
The paper investigates the extent to which stock market development enhances private investment in Ghana. Quarterly times series data for the period 1991(Q1) to 2011(Q4) are used. Stock market development is proxy by market capitalization. The paper adopts the Dynamic Ordinary Least Squares (DOLS) method of estimation. The results for deposit interest rates, GDP per capita, and public investment confirm complementarity hypothesis, accelerator principle, as well as “crowding-in” effect for Ghana in the long-run in their respective cases. Market capitalization also increases private investment in the long-run. However, inflation reduces private investment. In the short-run, one quarter lag and two quarters lag values of private investment and public investment respectively increases private investment, while one quarter lag value of market capitalization reduces current levels of private investment. The paper recommends further development of the stock market since doing so will attract more investors and ultimately enhance private investment.